PRESCRIPTION AUDIT USING THE WORLD HEALTH ORGANIZATION PRESCRIBING INDICATORS FOR INDOOR PATIENTS TREATED UNDER CMAAY/PMJAY INSURANCE SCHEMES IN A TERTIARY CARE TEACHING HOSPITAL - SACHDEV, DEVENDER; SALWE, KARTIK JANARDAN; DEV, ANOOP; SINGHA, BINITA; AMBING, HAGE (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: This study focused on the prescriptions audit of indoor patients treated under Pradhan Mantri Jan Arogya Yojana (PMJAY) and Chief Minister Arogya Arunachal Yojana (CMAAY) insurance schemes as per the World Health Organization (WHO) prescribing indicators. Materials and Methods: Retrospective cross-sectional study was conducted and the prescriptions of around 960 patients were analyzed who were treated from June 2020 to December 2020 under CMAAY/PMJAY insurance schemes at Tomo Riba institute of Health and Medical Sciences in Arunachal Pradesh. Study was conducted in five departments and Information was collected through the review of case sheets. The post-operative day prescription was analyzed for the patients who have undergone surgery and the patients who were managed conservatively; admission day prescription was analyzed using the WHO core drug prescribing indicators. Following data were analyzed. (1) Average no of drugs prescribed per encounter; (2) percentage of encounter having antibiotic; (3) percentage of drugs prescribed by generic name; (4) percentage of encounters with an injection; and (5) percentage of drugs prescribed from the essential drug list. Results: A total of 960 indoor patients treated under five departments, out of which 359 (37.4%) treated under general surgery, 383 (39.9%) under Obstetrics and Gynecology department, 65 (6.8%) under ENT department, 68 (7.1%) under orthopedics department, and 85 (8.9%) under General medicine department. All departments taken together, the average number of drugs used per patient was 4.91. Antibiotics were prescribed in 92.18% of the total patients when all departments were included, single antibiotic was used in 72.18%, two antibiotics in 17.29%, and three in 2.7% of the total patients. Overall, the generic names were written in 67.3% of the total drugs and the most commonly used route was parenteral route, in about 98.19% of the total prescribed drugs. From the essential drugs list, 89.33% of the total drugs were prescribed. Fixed drug combination was used in 13.59% of the total drugs prescribed. Conclusion: In our study, the percentage of prescriptions with average no of drugs per prescription, antibiotic used, injections used were much higher when compared to the WHO core prescribing indicators. The reason might be because we have analyzed the prescription of indoor patients and most of them were post-operative patients, so it is justified. While prescribing, the physicians and surgeons followed WHO essential drug list but use of generic names was in few prescriptions. The generic name use to be more emphasized, encouraged, and promoted.